FAKTOR DETERMINASI KEPUTUSAN INVESTASI EMAS PADA NASABAH GENERASI Z DAN GENERASI Y PRODUK TABUNGAN EMAS PEGADAIAN SYARIAH - Dinda Millenia Fitriansyah (2022)
The purpose of this study is to explain the effect of herding, risk tolerance, and income on gold investment decisions on generation Z and generation Y customers of tabungan emas Pegadaian Syariah on the Island of Java. Quantitative method is a research method used in this study which refers to numerical data. Primary data is used in this research by collecting questionnaires from 200 respondents. This research used 200 respondents of Generation Z and Generation Y Customers of Tabungan Emas Pegadaian Syariah on the Island of Java as subjects. Meanwhile, the data analysis technique used is multiple linear regression analysis, test the validity and reliability of the data, descriptive statistical analysis, classical assumptions test, and hypothesis testing. The result obtained within this research are herding has a positive and insignificant effect on gold investment decisions. Then, risk tolerance has a positive and significant effect on gold investment decision, income has a positive and significant impact on gold investment decision. So it can be concluded that partially, herding does not affect gold investment decisions, but is influenced by risk tolerance and income. Simultaneously, herding, risk tolerance, and income have a positive and significant influence on gold investment decisions for generation z and generation y customers of tabungan emas Pegadaian Syariah on The Island of Java. Keywords: sharia investment, herding, risk tolerance, income, gold investment decisions